Investigating the Interaction Between Form and Motion Processing: A Review of Basic Research and Clinical Evidence - Donato, Rita; Pavan, Andrea; Campana, Gianluca (Frontiers in Psychology, 2020)
A widely held view of the visual system supported the perspective that the primate brain is organized in two main specialized streams, called the ventral and the dorsal stream. The ventral stream is known to be involved in object recognition (e.g., form and orientation). In contrast, the dorsal stream is thought to be more involved in spatial recognition (e.g., the spatial relationship between objects and motion direction). Recent evidence suggests that these two streams are not segregated but interact with each other. A class of visual stimuli known as Glass patterns has been developed to shed light on this process. Glass patterns are visual stimuli made of pairs of dots, called dipoles, that give the percept of a specific form or apparent motion, depending on the spatial and temporal arrangement of the dipoles. In this review, we show an update of the neurophysiological, brain imaging, psychophysical, clinical, and brain stimulation studies which have assessed form and motion integration mechanisms, and the level at which this occurs in the human and non-human primate brain. We also discuss several studies based on non-invasive brain stimulation techniques that used different types of visual stimuli to assess the cortico-cortical interactions in the visual cortex for the processing of form and motion information. Additionally, we discuss the timing of specific visual processing in the ventral and dorsal streams. Fi-nally, we report some parallels between healthy participants and neurologically impaired patients in the conscious processing of form and motion.